Foxtail Millet (Setaria italica): A Detailed Review on Nutritional Value, Anti-Nutritive Value, Potential Health Benefits - Yadav Sakshi R; Sumitra Meena; Nikita Purbia (International Journal of Nutritions, 2024)
Millets are a diversified collection of small-seeded grasses that have been used as a primary source of grain for generations in various regions of Asia and Africa. Millets are a staple grain this is historically consumed in dry regions everywhere in the international. They are high in protein, fats, minerals, nutrients, and fiber.. Millets are highly nutritious grains rich in essential amino acids, minerals, and dietary fiber, offering health benefits such as managing diabetes and improving cardiovascular health. Key millet varieties embody foxtail millet (Setaria italica), proso millet (Panicum miliaceum), barnyard millet (Echinochloa spp.), finger millet (Eleusine coracana), pearl millet (Pennisetum glaucum), and small millet (Panicum sumatrense). Various processing methods like roasting, milling, germination, and fermentation are used to enhance the bioavailability of nutrients in millets by reducing anti-nutritional factors. Including millets in agricultural practices can help deal with the problem of hunger, enhance sustainable agriculture, and assist objectives concerning vitamins, food protection, and mitigating the outcomes of climate exchange. Millets possess exceptional nutritional value, being rich in protein, fiber, vitamins and minerals. Their inclusion in diets helps combat malnutrition and achieve Zero Hunger (SDG 2). These climate-resilient crops require fewer resources including water and contribute to Clean Water and Sanitation (SDG 6). Millets are also gluten-free, low glycemic index alternatives that promote Good Health and Well- being (SDG 3). In phrases of millet production, foxtail millet is ranked second globally and keeps maintaining a outstanding position. Its significance as a meals that is right for diabetics is widely known. It is rich in dietary fiber, minerals, micronutrients, protein, and has low glycemic index (GI).
Keywords: Anti- Nutritional factors; Foxtail Millet; Glycemic Index; Millet; Sustainable Development Goals